Experimental comparison on tribological pairs UHMWPE/TIAL6V4 alloy, UHMWPE/AISI316L austenitic stainless and UHMWPE/AL2O3 ceramic, under dry and lubricated conditions. (April 2016) - Ruggiero, Alessandro; D׳Amato, Roberto; Gómez, Emilio; Merola, Massimiliano
Abstract: Friction and wear behavior of ultra-high molecular weight polyethylene (UHMWPE) sliding against TiAl6V4 alloy, against AISI316L austenitic stainless steel and against Al2 O3 ceramic under dry and lubricated conditions was investigated. Tests were conducted by using a reciprocating pin-on-flat tribometer with several applied normal loads. Lubricated sliding tests were carried out with a fluid containing a large amount of sodium hyaluronate. The worn surfaces of the UHMWPE were examined with a 3D confocal microscopy. The tribological performances of pairs UHMWPE/AISI316L, UHMWPE/TiAl6V4 and UHMWPE/Al2 O3 were also investigated for the purpose of comparison. The results were interpreted on the basis of the evolution of the friction coefficient and worn surfaces in order to understand the acting wear mechanisms. Highlights: Experimental analysis of tribological behavior of UHMWPE against TIAL6V4 Alloy. Experimental analysis of tribological UHMWPE behavior against AISI316L. Experimental analysis of tribological behavior of UHMWPE against AL2 O3 ceramic. We used a reciprocating bio-tribometer in dry and lubricated conditions (Hyalgan®). The friction coefficient and the wear were measured.